Investigating the Use of Oral Corrective Feedback in Teaching Speaking for the Seventh Grade of EFL Students - Tumini, Tumini; Trisanti, Novia (Universitas Pahlawan Tuanku Tambusai, 2025)
Oral corrective feedback (OCF) plays an important role in helping to develop students’ speaking skills in the EFL classroom. In practice, the application of OCF varies depending on teaching style and classroom conditions. This research investigates the types and implementations of OCF by seventh-grade English teachers in a private school, MTs NU Mranggen, in teaching speaking skills. This qualitative single case study used observation and semi-structured interviews. The results showed that teachers used three types of OCF: rephrasing, explicit correction, and request for clarification, with rephrasing being the most frequently used as it allowed teachers to correct errors without interrupting the interaction process. In addition, OCF often appeared at the main activity stage, especially when students interacted with the teacher. Based on the findings, it is suggested that teachers use OCF techniques in a more planned way to improve students’ speaking ability in the EFL classroom.